2000
DOI: 10.1016/s0022-5223(00)70086-9
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor–β1 gene transfer ameliorates acute lung allograft rejection

Abstract: The feasibility of using gene transfer techniques to introduce novel functional genes in the setting of lung transplantation is demonstrated. In this model of rat lung allograft rejection, gene transfer of transforming growth factor-beta1 resulted in temporary but significant improvements in lung allograft function and acute rejection pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…This could be attributed to the immunosuppressive effect of n-3 PUFA. TGF-β1 is known as an anti-inflammatory cytokine [36,37]. Previous studies have shown that low plasma n-3 PUFA level is associated with high TGF-β expression in a normal population [36].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the immunosuppressive effect of n-3 PUFA. TGF-β1 is known as an anti-inflammatory cytokine [36,37]. Previous studies have shown that low plasma n-3 PUFA level is associated with high TGF-β expression in a normal population [36].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the possibility that administration of a TGF-␤-inhibitory agent such as pirfenidone could potentially cause more acute rejection. 25,26 To address this issue, we delayed giving pirfenidone until Days 9 and 16 in some of our experimental animals. At this point, the acute cellular response would have begun, but the development of granulation tissue would be none to minimal.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that pirfenidone may be worthy of further evaluation for its effectiveness in preventing or ameliorating OB in lung transplant recipients. Pirfenidone's mechanism of action probably involves TGF-␤; however, pirfenidone is known to interfere with other mediators of fibrosis [23][24][25][26][27][28][29][30][31][32][33][34] and thus additional investigations of its effects on these and other mediators of rejection are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…lung transplantation. 5,6 Moreover, tolerance has been induced in an orthotopic lung transplant model in association with elevated serum levels of TGF-␤, although alloimmune responses were restored with the administration of neutralizing antibodies to TGF-␤. 7 Despite its potent anti-inflammatory properties that would otherwise seem desirable in transplantation, TGF-␤ has been implicated in the pathogenesis of allograft rejection, and is markedly overexpressed in patients with chronic liver, kidney, and heart rejection.…”
mentioning
confidence: 99%